Pattern of the Use of Physical Restraint on Psychiatric Inpatients in University Malaya Medical Centre - Gan, C.K.; Jambunathan, S.T.; Jesjeet, S.G. (2003)
Restraint and seclusion is a commonly used management technique In manypsychiatric Institutes worldwide. However, this practice is viewed by many as aviolation of human rights.In order to understand the circumstances surrounding thispractice, a descriptive study on this subject was conducted at the University MalayaMedical Centre over a three month period, analyzing the socio-demographic characteristics, diagnoses, patterns of restraint and the indications. Results showed that patients with Schizophrenia were the most frequently restrained (42.5%) and the commonest indication for restraint was for being physically assaultative (25.3%).Approximately 50% of patients on electroconvulsive therapy (ECT) werealso restrainedprior to ECT. Most restraints occurred during the night shift with the four pointrestraint being the commonest method. The above results are discussed criticallyand based on these findings suggestions are made how physical restraint inpsychiatry can be reduced.